Evolutionary paleoecology : the ecological context of macroevolutionary change - Allmon, Warren D.; Bottjer, David J. (Columbia University Press, 2001)
One of the most important questions we can ask about life is "Does ecology matter?" Most biologists and paleontologists are trained to answer "yes," but the exact mechanisms by which ecology matters in the context of patterns that play out over millions of years have never been entirely clear. This book examines these mechanisms and looks at how ancient environments affected evolution, focusing on long-term macroevolutionary changes as seen in the fossil record